(i) C(X +Y,Z)= C(X,Z)+C(Y,Z), where X and Y are two random vectors of the same dimension and C(X,Z)=C(Z,X).
(ii) If m=n, V(X+Y) =V(X) + V(Y)+ 2C(X,Y).
Let
"X=\\left(X_1 ,....X_n \\right)"
"Y=\\left(Y_1 ,....Y_n \\right)"
"Z=\\left(Z_1 ,....Z_n \\right)"
be any random vectors on the same probability space "P=(\\varOmega, \\varSigma, \\mu)"
Then covatiance matrix C(X+Y,Z)=
"E\\left( (X+Y-E(X+Y))(Z-EZ)^T \\right)=\\\\\nE\\left( (X+Y-EX-EY))(Z-EZ) ^T \\right)=\\\\\nE\\left( (X-EX)+(Y-EY))(Z-EZ)^T \\right)=\\\\\nE\\left( (X-EX)(Z-EZ)^T + (Y-EY)(Z-EZ)^T \\right)=\\\\\nE\\left( (X-EX)(Z-EZ)^T \\right)+E\\left( (Y-EY)(Z-EZ)^T \\right)=\\\\\nC(X,Z)+C(Y,Z)"
First identity is proved.
During proving property of random matrices V,W : E(V+W)=EV+EW have being applied.
2) For proving second statement we need in additional condition C(X,Y)=C(Y,X)
"V(X+Y)=C(X+Y,X+Y)=]by\\space 1]=C(X,X)+C(X,Y)+C(Y,X)+C(Y,Y)=\\\\\n=V(X)+V(Y)+C(X,Y)+C(X,Y)^T=\\\\\n[by\\space asymption \\space C(X,Y)=C(Y,X)]= \\\\\nV(X)+V(Y)+2\\cdot C(X,Y)"
Comments
Leave a comment